A U5 small nuclear ribonucleoprotein particle protein involved only in the second step of pre-mRNA splicing in Saccharomyces cerevisiae. - Horowitz, D S (1993)
The PRP18 gene, which had been identified in a screen for pre-mRNA splicing mutants in Saccharomyces cerevisiae, has been cloned and sequenced. Yeast strains bearing only a disrupted copy of PRP18 are temperature sensitive for growth; even at a low temperature, they grow extremely slowly and do not splice pre-mRNA efficiently. This unusual temperature sensitivity can be reproduced in vitro; extracts immunodepleted of PRP18 are temperature sensitive for the second step of splicing. The PRP18 protein has been overexpressed in active form in Escherichia coli and has been purified to near homogeneity. Antibodies directed against PRP18 precipitate the U4/U5/U6 small nuclear ribonucleoprotein particle (snRNP) from yeast extracts. From extracts depleted of the U6 small nuclear RNA (snRNA), the U4 and U5 snRNAs can be immunoprecipitated, while no snRNAs can be precipitated from extracts depleted of the U5 snRNA. PRP18 therefore appears to be primarily associated with the U5 snRNP. The antibodies against PRP18 inhibit the second step of pre-mRNA splicing in vitro. Together, these results imply that the U5 snRNP plays a role in the second step of splicing and suggest a model for the action of PRP18.